The Ambition And Power In Caryl Churchill’s Top Girls - Tiara Auliya Salsabillah; Alya Yumna Adristi; Mutiara Vidrin Rittiauw (Universitas Palangka Raya, 2024)
This writing aims to describe the ambition and power of feminist in Caryl Churchill’s Top Girls. Churchill reveals how women are ambitious to achieve power by taking male roles in the middle of the patriarchal system. Churchill addresses feminism issues from the class distinction and sacrifices similar to the current problems. This writing traces the sacrifice of the main character, Marlene, in reaching her goal as a career woman. This writing used qualitative methods to explore the object and inventory techniques to collect the data.